Análisis de la influencia de la comunicación interna, para el desarrollo de las relaciones públicas en la clínica Medina de Guayaquil - Dávila Cedeño, Signey Karolina (2019)
The research project is oriented towards the analysis of the influence of Internal Communication, for the development of Public Relations in the Medina Clinic of Guayaquil, and its impact on the staff that works, for this was approached from a qualitative-quantitative approach in a field environment, where the internal and external staff gave their opinions and perspectives regarding the functioning of the internal communication, interviews were applied to the Director of the place and to different professionals of the area of national and international communication and surveys to patients and staff who works in the entity. One of the main objectives is to cover the information needs and the shortcomings in communication processes with the internal public of Clínica Medina……..